2006
DOI: 10.1590/s0100-879x2006000700002
|View full text |Cite
|
Sign up to set email alerts
|

Ureases display biological effects independent of enzymatic activity: Is there a connection to diseases caused by urease-producing bacteria?

Abstract: Ureases are enzymes from plants, fungi and bacteria that catalyze the hydrolysis of urea to form ammonia and carbon dioxide. While fungal and plant ureases are homo-oligomers of 90-kDa subunits, bacterial ureases are multimers of two or three subunit complexes. We showed that some isoforms of jack bean urease, canatoxin and the classical urease, bind to glycoconjugates and induce platelet aggregation. Canatoxin also promotes release of histamine from mast cells, insulin from pancreatic cells and neurotransmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 57 publications
0
25
0
2
Order By: Relevance
“…The enzymatic function of urease is to produce ammonia and carbon dioxide from urea. However, recent studies on plant ureases suggest that they play a role in defense mechanisms and have biological function independent of their enzymatic activity (Olivera-Severo et al 2006). The A. baumannii urease gene may play a similar role.…”
Section: Smith Et Almentioning
confidence: 99%
“…The enzymatic function of urease is to produce ammonia and carbon dioxide from urea. However, recent studies on plant ureases suggest that they play a role in defense mechanisms and have biological function independent of their enzymatic activity (Olivera-Severo et al 2006). The A. baumannii urease gene may play a similar role.…”
Section: Smith Et Almentioning
confidence: 99%
“…6,15 Both bacterial and plant ureases display several biological activities that are independent of their ureolytic activity. [16][17][18][19][20] For example, enzymatic activity is not involved in platelet aggregation and antifungal activities of plant and microbial ureases. 17,19,20 Similarly, the lethal activity of canatoxin (an isoform of JBU) in mice and the insecticidal activity of plant ureases are independent of ureolytic activity.…”
mentioning
confidence: 99%
“…Urease, a cytoplasmic enzyme, catalyzes the hydrolysis of urea to form ammonia and carbon dioxide, providing both an increase in pH and a readily assimilated source of nitrogen (32). Recent studies have shown that bacterial ureases may encode other biological activities independently of their ureolytic activity, such as induction of platelet aggregation and activation of lipooxygenases (37). The EHEC ure gene cluster, ureDABCEFG, contains the seven genes necessary to form active urease.…”
mentioning
confidence: 99%